2019
DOI: 10.3390/app9020340
|View full text |Cite
|
Sign up to set email alerts
|

Secretory Laccase from Pestalotiopsis Species CDBT-F-G1 Fungal Strain Isolated from High Altitude: Optimization of Its Production and Characterization

Abstract: Microorganisms producing laccases may be used for the pretreatment of lignocellulosic biomass to recover fermentable sugar. Very few fungi and other microbes growing in high altitudes have been tested for this purpose. As part of this study, we have collected soil samples from different parts of the Kathmandu Valley and the Rautah at district of Nepal (1600 to 2303 m above sea level) and successfully cultured 53 different isolates of microorganisms. Among the 53 isolates obtained 30 were Actinomycetes, 20 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…During our screening process, 15 bacteria, 7 basidiomycete fungi, and 5 lower fungi tested positive for laccase activity, and all these isolates were also positive for peroxidases activity. Rich supplements of specific substrates like phenolic substrates indicate secretion of ligninolytic enzymes was proven in other studies [ 34 – 36 ]. All the ligninolytic enzyme-positive strains tested for cellulases activity by congo red-CMC produced variable zones (CMC clearance) around their colony, and the decolorized zones of congo red-CMC demonstrated the ability to degrade CMC [ 37 ].…”
Section: Resultsmentioning
confidence: 78%
“…During our screening process, 15 bacteria, 7 basidiomycete fungi, and 5 lower fungi tested positive for laccase activity, and all these isolates were also positive for peroxidases activity. Rich supplements of specific substrates like phenolic substrates indicate secretion of ligninolytic enzymes was proven in other studies [ 34 – 36 ]. All the ligninolytic enzyme-positive strains tested for cellulases activity by congo red-CMC produced variable zones (CMC clearance) around their colony, and the decolorized zones of congo red-CMC demonstrated the ability to degrade CMC [ 37 ].…”
Section: Resultsmentioning
confidence: 78%
“…With the addition of inducer Tannic Acid, the laccase gene's expression rises, and laccase production increases in the growth medium (41) . It has previously been observed that binding of sodium azide to the types 2 and 3 copper sites affects internal electron transfer, decreasing laccase activity and that formaldehyde, as an organic solvent, alters the pH of an aqueous solution, resulting in lower enzyme output (42) .…”
Section: Effect Of Ph Temperature Activators and Inhibitors On Laccas...mentioning
confidence: 99%
“…Supplements with specific phenolic substrates indicate extracellular secretion of ligninolytic enzymes which was proven in different research. [44][45][46] All the cellulolytic isolates were tested for cellulase activity by congo red-CMC agar and malachite green CMC-agar plate assay that produced non-homogenous clear zones (CMC clearance) and the decolorized zones of congo red CMC-agar (Figure 3b) and malachite green CMC-agar (Figure 3a) demonstrated the cellulosedegrading capacity 47 and dye decolorization ability. Cellulase plays a crucial role in the breakdown of lignocellulosic biomass to release the fermentable sugar monomers that are then used in enzymatic saccharification for the production of biofuel.…”
Section: Isolation and Qualitative Screening Of Lignocellulolytic Iso...mentioning
confidence: 99%